Disinflation Programs: Lessons from 2001 Crisis in Turkey - KAYIKÇI, Fazıl (Asian Journal of Empirical Research, 2013)
Turkey initiated an exchange based disinflation program at December 1999 which is supervised by IMF and had to abandon it at February 2001, before the 18 month time of the program is completed. The failure of the program was mainly due to its design flaw beside the other effects like the inability of Turkish government to apply the program properly or the external macroeconomic events. This paper focuses of two important weaknesses of the program, which are the lack of proper exit strategy and the liquidity generating mechanism of the Central Bank, and suggests an earlier exit and capital controls as cures.